1997
DOI: 10.1021/bi9709654
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Water Oxidizing Complex in Leaves of the dgd1 Mutant of Arabidopsis thaliana Deficient in the Galactolipid Digalactosyldiacylglycerol

Abstract: The primary biochemical defect in the genetically well characterized dgd1 mutant of Arabidopsis thaliana causes a 90% reduction in the relative amount of the galactolipid digalactosyldiacylglycerol (DGDG). To study the effect of this DGDG deficiency on photosystem II (PS II), time-resolved transients of laser-flash-induced changes of the relative fluorescence quantum yield Fvar,rel(t) were measured in whole leaves from wild-type and the dgd1 mutant. The results obtained reveal (i) in untreated leaves the decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…Structural analysis of crystallized protein complexes revealed that galactolipids are also found within the structures of PSI and PSII, light-harvesting complex II (LHCII), and cytochrome b 6 /f (Jordan et al, 2001;Stroebel et al, 2003;Liu et al, 2004;Loll et al, 2005;Jones, 2007). MGD and DGD play crucial roles in photosynthetic light reactions, and this is in agreement with results obtained from the analysis of galactolipid-deficient Arabidopsis (Arabidopsis thaliana) mutants (Härtel et al, 1997;Reifarth et al, 1997;Guo et al, 2005). The dgd1 mutant of Arabidopsis contains approximately one-tenth of the wild-type amount of DGD (Dö rmann et al, 1995).…”
supporting
confidence: 86%
“…Structural analysis of crystallized protein complexes revealed that galactolipids are also found within the structures of PSI and PSII, light-harvesting complex II (LHCII), and cytochrome b 6 /f (Jordan et al, 2001;Stroebel et al, 2003;Liu et al, 2004;Loll et al, 2005;Jones, 2007). MGD and DGD play crucial roles in photosynthetic light reactions, and this is in agreement with results obtained from the analysis of galactolipid-deficient Arabidopsis (Arabidopsis thaliana) mutants (Härtel et al, 1997;Reifarth et al, 1997;Guo et al, 2005). The dgd1 mutant of Arabidopsis contains approximately one-tenth of the wild-type amount of DGD (Dö rmann et al, 1995).…”
supporting
confidence: 86%
“…This might be one explanation for the fact that ␣Gal␤GalDG is the preferred dihexosyldiacylglycerol lipid for the functional stabilization of pigment-protein complexes. In addition, ␣Gal␤GalDG deficiency in the dgd1 mutant was previously shown to affect the integrity of PSI, PSII, and the oxygen evolving complex (37,38). Furthermore, ␣Gal␤GalDG was recently identified in the crystal structure of PSII, and it is possible that this lipid is involved in PSII dimerization (39).…”
Section: Discussionmentioning
confidence: 98%
“…For these experiments data were collected between 150 s to 60 s following a single saturating flash. Data were analyzed using the equations outlined previously (23). In this mathematical treatment, three exponential decay components and a long-lived ( Ͼ 10 s) residual component were included.…”
Section: Methodsmentioning
confidence: 99%